A matemática presente nas profissões : uma proposta de trabalho para o ensino médio - Dias, Nathalia da Costa (2024)
Mathematics is present in the most varied educational, social and professional fields. Its use as a tool, teaching area or methodology can be seen in the resolution of everyday problems or in the development of technology throughout history. This research aimed to present the contributions of Mathematics in the most diverse possible professions, illustrating some meanings for contents that is currently taught up to the 1st year of high school in the state public school system. Through research, it was possible to highlight how Mathematics is inserted in some professions selected by the participants. After applying an initial questionnaire, preparing the work on Mathematics and Professions and data collection through a final questionnaire about this context, the students realized that Mathematics is in fact inserted in the professional scope, in careers that they did not imagine that its use would be important